NILAI ETNOPEDAGOGI PADA TRADISI UPACARA “MEPANGKONAN” DI DESA ADAT GESING KECAMATAN BANJAR KABUPATEN BULELENG (JURDIKSCA: Jurnal Pendidikan Agama Hindu Mahasiswa Pascasarjana, 2025)
ABSTRACT Tradition is a fixed price or treasure that cannot be bought with money, property or other things and this tradition is a form of national identity. They really appreciate the traditions inherited from their ancestors. One of them is the Mepangkonan tradition which they carry out every six months at the time of the sixth tilem. This Mepangkonan ceremony tradition is a form of offering (Yadnya) to Sang Hyang Widhi Wasa in the hope that they will be protected from negative influences. In the Mepangkonan tradition, there are many things that can be learned by the people of Gesing Village, especially teenagers, because in the Mepangkonan tradition there are ethnopedagogical values that are very interesting to learn as successors to the traditions in Gesing Village. This research Mepangkonan uses qualitative research methods using theories, namely structural functional theory, ritual, and ethnopedagogical theory. The techniques used to obtain data are observation, interviews, literature study and documentation and analyzed using data triangulation techniques so that valid and holistic conclusions are obtained. The results of the analysis from this research can be described as follows: The objectives of maintaining the Mepangkonan tradition include, creating a religious Gesing Village community, creating a harmonious Gesing Village community, the form of the Mepangkonan Tradition related to elements relating to, background, place and time, facilities and infrastructure, parties involved in the procession Mepangkonan Tradition. The ethnopedagogical values contained in the Mepangkonan tradition are the value of piety in tradition, the value of togethernessand social solidarity and the value of preservation in ceremonial traditions.
Keywords: Keywords: Ethnopedagogical Values, Mepangkonan Tradition.